TLR9 and NF-κB are partially involved in activation of human neutrophils by Helicobacter pylori and its purified DNA. - Lourdes Alvarez-Arellano; Pedro Cortés-Reynosa; Norma Sánchez-Zauco; Eduardo Salazar; Javier Torres; Carmen Maldonado-Bernal (PLoS ONE)
Helicobacter pylori infection represents one of the most common bacterial infections worldwide. The inflammatory response to this bacterium involves a large influx of neutrophils to the lamina propria of the gastric mucosa. However, little is known about the receptors and molecular mechanisms involved in activation of these neutrophils. In this study, we aimed to determine the role of toll-like receptor 9 (TLR9) in the response of human neutrophils to H. pylori and purified H. pylori DNA (Hp-DNA). Neutrophils were isolated from the blood of adult volunteers and challenged with either H. pylori or Hp-DNA. We found that both, H. pylori and Hp-DNA induced increased expression and release of IL-8. Furthermore, we showed that TLR9 is involved in the induction of IL-8 production by H. pylori and Hp-DNA. IL-8 production induced by H. pylori but not by Hp-DNA was partially mediated by NF-κB. In conclusion, this study showed for first time that both, H. pylori and Hp-DNA activate TLR9 and induce a different inflammatory response that leads to activation of neutrophils.